PEMANFAATAN LABU SIAM DAN KELOPAK ROSELLA DALAM PEMBUATAN SELAI - Kurniawan, Yogi; Johan, Vonny Setiaries; Hamzah, Faizah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Fruit jam is a semi-wet food processed product from a mixture of fruit juice and sugar. The purpose of this research was to get the best formulation of chayote and roselle petal evaluate in the jam quality. Thisresearch useda Completely Randomized Design experiment with five treatments and three replications. The treatmentswere LSR1 (chayote puree and roselle petal puree 90:10), LSR2 (chayote puree and rosella petal puree 80:20), LSR3 (chayote puree and roselle petal puree 70:30) and LSR4 (chayote puree and roselle petal puree 60:40). The value of observation were analyzed using Analysis of Varians and followed by Duncan’s New Multiple Range Test on 5% level. The result showed that the ratio ofchayote and roselle petals puree significantly affected acidity, moisture, ash , pectin and sucrose contents, antioxidant activity, descriptive test of color, flavour, taste and texture. The best treatment was LSR4 with moisture content 19.42%, ash content 0.26%, pectin 2.63%, sucrose 64.80%, antioxidantactivity 9.40 ppm, dark red color, flavourful rosella, sweet taste little acid, and soft texture of jam. Keyword: Jam, chayote,rosella petal.